Cross-cultural adaptation and validation of the Persian version of the Intermittent and Constant Osteoarthritis Pain Measure for the knee - Sara Hojat Panah; Hamze Baharlouie; Zahra Sadat Rezaeian; Gilian Hawker (Wolters Kluwer Medknow Publications, 2016)
Objective: The present study aimed to translate and evaluate the reliability and validity of the Persian version of the 11-item Intermittent and Constant Osteoarthritis Pain (ICOAP) measure in Iranian subjects with Knee Osteoarthritis (KOA). Materials and Methods: The ICOAP questionnaire was translated according to the Manufacturers Alliance for Productivity and Innovation (MAPI) protocol. The procedure consisted of forward and backward translation, as well as the assessment of the psychometric properties of the Persian version of the questionnaire. A sample of 230 subjects with KOA was asked to complete the Persian versions of ICOAP and Knee injury and Osteoarthritis Outcome Score (KOOS). The ICOAP was readministered to forty subjects five days after the first visit. Test-retest reliability was assessed using Intraclass Correlation Coefficient (ICC), and internal consistency was assessed by Cronbach's alpha and item-total correlation. The correlation between ICOAP and KOOS was determined using Spearman's correlation coefficient. Result: Subjects found the Persian-version of the ICOAP to be clear, simple, and unambiguous, confirming its face validity. Spearman correlations between ICOAP total and subscale scores with KOOS scores were between 0.5 and 0.7, confirming construct validity. Cronbach's alpha, used to assess internal consistency, was 0.89, 0.93, and 0.92 for constant pain, intermittent pain, and total pain scores, respectively. The ICC was 0.90 for constant pain and 0.91 for the intermittent pain and total pain score. Conclusion: The Persian version of the ICOAP is a reliable and valid outcome measure that can be used in Iranian subjects with KOA.